Evaluation of the dyeability of hemp fabric with Anatolian black pine (Pinus nigra subsp. Pallassiana) and Scots pine (Pinus sylvestris L.) - PARS, ABDULKADİR (My University, 2023)
The development of more sustainable textile dyeing techniques includes a lot of potential in utilizing bio-based plant-derived colorants. Hemp fabric has been dyed with an aqueous extract of pine cones at various dye concentrations to produce a brownish to darker color. Agricultural waste specimens, Anatolian black pine (Pinus nigra subsp. Pallassiana), and Scots pine (Pinus sylvestris L.) cones were used as natural dye sources on a sustainable basis. The dyed hemp fabrics were analyzed by different analytical and technical methods such as CIE L*a*b*, high-pressure liquid chromatography–diode-array detection, and scanning electron microscopy with an energy dispersive X-ray spectrometer. The color characteristics of all the dyed fabrics were measured by a CIE L*a*b* spectrophotometer. The reversed-phase high-pressure liquid chromatography–diode-array detection method with the diode-array detection method was utilized for the identification of the components of dyes present in the dyed fabrics. Scanning electron microscopy with an energy dispersive X-ray spectrometer was used for imaging and elemental analysis of the surfaces of the dyed hemp fabrics. This work has created a novelty direct dyeing method with pine cones without using any mordants and to promote the use of agricultural waste. The fastness values of washing, rubbing, and light were assessed and contrasted. The fastness results were good in general. Washing fastness values were excellent and the same for all fabrics between 4 and 5. Rubbing fastness is also generally good and of the desired grade. The chemical compositions of hemp and pine cones, as well as the formation of dyestuff fiber, were investigated by using Fourier transform infrared analysis.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)